(untitled) (Al-Qamar, 2019)
The term Islamophobia is combination of two words “Islam and phobia” with an additional “O” to connect the two expressions. As the word phobia means to hate, to repel or to fear without any reason, so, Islamophobia means hate or fear for Islam and always attaching negative connotations with Islam. This article is an effort to comprehend contemporary Islamophobia, prevailing in western world specifically and worldwide generally. It begins with detailing various incidents of Islamophobia. Around 15 reported incidents of fear of Islam, Islamic values and Islamic symbols have been documented. It also identifies the causes of Islamophobia. The two main sources recognized are “doubts about Islam” and “Role of media”. Doubts about Islam stem from several reasons which include history, increasing Muslim population, migration to the west and attaching Islam with terrorism. The role of western media and media in Muslim majority countries is of extreme concern in this regard. Western media usually attaches the notions of fear, doubt, terrorism and inhumanity with Islam and Muslims. While significant majority of media in Muslim countries follow the trodden path of western media and are unable to present or defend the Muslim narrative. The article also briefly summarizes the impacts of Islamophobia on Muslims and the existing global world. Finally, several solutions to this psychological fear has been discussed. Two most important solutions are developing positive relationships with media and giving our response to doubts and fears related to Islam in polite and sensible way.